Kierkegaard on authority and leadership: Political logic in religious thought - Khan, Abrahim H. (Sophia, 1994)
This paper examines a political theory implict in Kierkegaard's critique of the novel Two Ages. To achieve that aim, it views Kierkegaard as a political radical relative to modern liberalism and aristocratic conservatism of the 1840's in Denmark, by juxtaposing him to Locke. Basic to the theory is a notion of individuality which relies on three interlocking concepts: will, equality, and autonomy. That notion in turn supports ideas of authority and leadership that throw further light on Kierkegaard's understanding of the relation between religion and politics and suggests what is central to the political logic operative in the critique in his publication Literary Review.